Study of transformation of complex business associations to ecosystems - Maev, Dmitry Vladimirovich; Valentinovna Iudina, Svetlana (Nexo Revista Científica, 2022)
The new reality, determined, on the one hand, by the complexity and non-linearity of socio-economic relations and, on the other hand, by the development of digitalization and the expanding possibilities of integration of various processes, requires new approaches to the study of entrepreneurial forms and associations. Network and cluster scientific methodologies were quite revolutionary at the time but remain quite productive. The authors of the article investigate the evolution of views and discuss the feasibility of applying an ecosystem approach to the study of large business structures such as "group of companies". The logic is as follows: the larger the business association, the more it is embedded in the environment, formally (legally) located behind the contour of this structure. Therewith, it is important to take into account the current trends in the development of the ecosystem approach, the specifics and structure of the group of companies. The article attempts, based on a combination of inductive and deductive methods, to determine the prospects for possible research directions of Russian groups of companies based on an ecosystem approach.